Performance Enhancement of Hybrid Energy Devices Using Cooling Patches - Jaehwan Lee; Kyoungah Cho; Yoonbeom Park; Sungeun Park; Hee-eun Song; Sangsig Kim (International Journal of Photoenergy)
In this study, we demonstrated the enhancement of the output power of a hybrid energy device (HED) using a cooling patch that does not consume any external electric power. The HED consisted of a photovoltaic cell (PVC) and a thermoelectric generator (TEG); the cooling patch was attached to the TEG. When the PVC was exposed to solar irradiance, the cooling patch lowered the temperature of the PVC and increased the thermal gradient across the TEG, thereby increasing the output power. For an HED with a cooling patch at an irradiance of 1000 W/m2, the output power increased to 24.2 mW, as compared to the output power of 19.9 mW for an HED without any cooling patch.